Odpowiedź :
(4 - a) - (-10) = -6
4 - a + 10 = -6
14 - a = -6
-a = -6 - 14
-a = -20
a = 20
Sprawdzenie:
(4 - a) - (-10) = -6
(4 - 20) - (-10) = -6
- 16 + 10 = -6
-6 = -6
(a + 1) - (-8) = -9
a + 1 + 8 = -9
a + 9 = -9
a = -9 - 9
a = -18
Sprawdzenie:
(a + 1) - (-8) = -9
(-18+1) -(-8) = -9
-17 + 8 = -9
-9 = -9
(4 - a) - (-10) = -6
4-a+10=-6
-a+4+10=-6
-a+14=-6
-a=-6-14
-a=-20 |·(-1)
a=20
spr
(4-20)-(-10)=-6
-16+10=-6
-6=-6
L=P
(a + 1) - (-8) = -9
a+1+8=-9
a+9=-9
a=-9-9
a=-18
spr
(-18+1)-(-8)=-9
-17+8=-9
-9=-9
L=P